Lamotrigine kidney distribution in male rats following a single intraperitoneal dose - Castel-Branco, M. M. (2004)
As it has been previously shown that lamotrigine (LTG) accumulates in the kidney of male rats, the purpose of the present investigation was to characterize the kidney profiles of LTG and its kidney distribution pattern in male rats, in order to confirm if a preferential distribution exists and to analyse if it does or does not affect the LTG systemic pharmacokinetics. Adult male Wistar rats were intraperitoneally injected with 5, 10 and 20 mg/kg of LTG. The concentration–time profiles of LTG in plasma and whole kidney were determined over 120 h postdose. The distribution of LTG in the rat kidney was investigated in another group of rats by measuring LTG levels in the renal cortex and medulla. The LTG plasma concentration–time profiles revealed a linear relationship with dose. However, a slight increase in the LTG elimination halflife with dose was observed. In contrast, a nonlinear relationship was established between LTG kidney levels and the dose administered. Consequently, nonparallel patterns were observed between LTG plasma and kidney profiles. The LTG kidney distribution pattern revealed an accumulation of LTG in the renal cortex. The present study demonstrated that LTG distributes preferentially to the kidneys of the male rat in a dose-dependent manner and suggests that such distribution may slightly affect the systemic kinetics of the drug.